Micronutrient metal speciation is controlled by competitive organic chelation in grassland soils. (May 2018) - Boiteau, Rene M.; Shaw, Jared B.; Pasa-Tolic, Ljiljana; Koppenaal, David W.; Jansson, Janet K.
Abstract: Many elements are scarcely soluble in aqueous conditions found in high pH environments, such as calcareous grassland soils, unless complexed to strong binding organic ligands. To overcome this limitation, some plants and microbes produce chelators that solubilize micronutrient metals such as Fe, Ni, Cu, and Zn from mineral phases. These complexes are taken up by organisms via specific membrane receptors, thereby differentially impacting the bioavailability of these metals to the plant and microbial community. Although the importance of these chelation strategies for individual organisms has been well established, little is known about which pathways coexist within rhizosphere microbiomes or how they interact and compete for metal binding. Identifying these metallophores within natural ecosystems has remained a formidable analytical challenge due to the vast diversity of compounds and poorly defined metabolic processes in complex soil matrices. Herein, we employed recently developed liquid chromatography (LC) mass spectrometry (MS) methods to characterize the speciation of water-soluble dissolved trace elements (Fe, Ni, Cu, and Zn) of soils from native tallgrass prairies in Kansas and Iowa. Both plant and fungal metallophores were identified, revealing compound-specific patterns of chelation to biologically essential metals. Numerous metabolites typically implicated in plant Fe acquisition and homeostasis, including mugineic acids, deoxymugineic acid, nicotianamine, and hydroxynicotianamines, dominated the speciation of divalent metals such as Ni, Cu, and Zn (2–90 pmol/g soil). In contrast, the fungal siderophore ferricrocin was specific for trivalent Fe (7–32 pmol/g soil). These results define biochemical pathways that underpin the regulation of metals in the grassland rhizosphere. They also raise new questions about the competition of these compounds for metal binding and their bioavailability to different members of the rhizosphere population. Small structural modifications result in significant differences in metal ligand selectivity, and likely impact metal uptake within the rhizosphere of grassland soils. Graphical abstract: Highlights: A new LCMS approach enabled the identification of metallophores in soil. These metal binding metabolites were quantified in tallgrass prairie soils. Plant phytosiderophores dominated Ni, Cu, and Zn binding. Both phytosiderophores and fungal siderophores chelated bioavailable Fe.